Brucellosis laboratory tests in Syria: what are their diagnostic efficacies in different clinical manifestations? - Yara Alsayed; Fawza Monem (Journal of Infection in Developing Countries)
Introduction: Diagnosis of brucellosis in Syria is based on the presence of compatible symptoms in addition to positive agglutination results. This study investigated the potential of culture, ELISA and real-time PCR to support the diagnosis in different clinical manifestations of brucellosis.